Charge transport optimisation in SnO2 nanoparticles via Zn doping to achieve a power factor of 83 μW/m.K2 - Najaf Abbas Khan; A. Ali; K. Mahmood; Muhammad Isram; S. Ikram (Results in Chemistry)
In this study, we have achieved a power factor value of 83×10−6W/(m.K2) by the optimized of electrical conductivity and the Seebeck coefficient. Zn-doped SnO2 nanoparticles were grown using a hydrothermal synthesis technique. Different concentrations of Zn atoms (x = 0.05 M, 0.1 M, 0.15 M, and 0.20 M) doped in SnO2 to control the carrier concentration and mobility for the optimized value of power factor. To confirm the successful doping of Zn atoms in the host SnO2 crystal, various primary measurements, such as XRD, Raman, and SEM. Hall measurements were performed. A strong increment in the electrical conductivity was observed from 28 to 156 S/cm with an increase in Zn doping concentration from 0.05 to 0.20 %. It is argued that Zn atoms effectively substitute the Sn atoms in the host SnO2 crystal and increased the number of charge carriers. These extra charge carriers contributed to the electrical conductivity and significantly enhanced its value. The Seebeck measurements revealed a decreasing trend of the Seebeck coefficient (−89 to-74 μV/K) with Zn doping concentration. The decrease in the Seebeck coefficient was justified due the inverse dependence of charge carrier concentration. Optimal values of the Seebeck coefficient and electrical conductivity have resulted in a very healthy value of power factor. The value of thermal conductivity is increased by increasing the Zn concentration. Overall Figure of merit (ZT) decreases as the Zn concentration is increased in the sample and the maximum value of ZT is for the undoped sample which is 0.55.